RADIOTECHNOLOGIES IN THE SERVICE OF HUMAN HEALTH - T. M. Chernova (Медицинский совет, 2018)
The introduction of advanced radio technologies into practical healthcare provides high-tech, qualified and reliable diagnostics. Radiation methods of visualizing the activity of organs and systems in real time are the basis of personified therapy and prevention of various pathological conditions. The evolution of telecommunication networks and mobile communication technologies has led to appearance a new direction in healthcare – distance medicine. Using of radio frequency identification systems, wireless medical telemetry, telemedicine not only improves the quality of life of patients, but also ensures the availability of medical care in any place and at any time.